PROSPECTS OF IMPROVING TREATMENT OF HSV INFECTED AT THE DENTIST’S - E. V. Nikolishyna; T.D. Bublii (Український стоматологічний альманах)
Herpetic infections are the most common and poorly controlled human infections. According to the National Institute of Health (NIH), by age 50, about 90% of adults have been exposed to the virus. The problem of herpetic infections attracts a lot of a physician’s attention. New methods and means of treatment of herpetic diseases will improve the effectiveness of preventive measures.